2017
DOI: 10.1136/jech-2016-208676
|View full text |Cite
|
Sign up to set email alerts
|

Reducing chemical exposures at home: opportunities for action

Abstract: Indoor environments can influence human environmental chemical exposures and, ultimately, public health. Furniture, electronics, personal care and cleaning products, floor coverings and other consumer products contain chemicals that can end up in the indoor air and settled dust. Consumer product chemicals such as phthalates, phenols, flame retardants and per- and polyfluorinated alkyl substances are widely detected in the US general population, including vulnerable populations, and are associated with adverse … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 38 publications
1
18
0
Order By: Relevance
“…This finding aligns with previous studies that have found various EDCs, such as phthalates, parabens and phenols, in commonly used products such as feminine hygiene products (Gao and Kannan 2020), hair products (Helm et al 2018), and other personal care products (Dodson et al 2012). Chemicals found in personal care products have also been found in in home air and dust (Rudel et al 2003;Zota et al 2017). Some of the consumer products also include pesticides that are used in or near homes and lawns, on children for lice control, or on pets, scenarios that present higher exposure potential.…”
Section: Exposure Findingssupporting
confidence: 91%
See 1 more Smart Citation
“…This finding aligns with previous studies that have found various EDCs, such as phthalates, parabens and phenols, in commonly used products such as feminine hygiene products (Gao and Kannan 2020), hair products (Helm et al 2018), and other personal care products (Dodson et al 2012). Chemicals found in personal care products have also been found in in home air and dust (Rudel et al 2003;Zota et al 2017). Some of the consumer products also include pesticides that are used in or near homes and lawns, on children for lice control, or on pets, scenarios that present higher exposure potential.…”
Section: Exposure Findingssupporting
confidence: 91%
“…Many of the chemicals in our E2-and P4-up chemical lists are pesticides (127 and 108, respectively), which is concerning, considering there are many ways that people can be exposed to pesticides, including aerial spraying, food residues, drinking water contamination, and use in the home. Indeed, many pesticides have been previously detected in environmental samples such as soil, water, indoor air and dust, food residues, and drinking water (Rudel et al 2003;Zota et al 2017). Consumer products are another major exposure source for these chemicals, including personal care products, such as hair dye, and materials used in buildings and furnishings, such as chemical flame retardants.…”
Section: Exposure Findingsmentioning
confidence: 99%
“…Similarly, reducing the exposure of children to household chemicals in ECE and FCCH environments has been recognized as an important area of intervention [13, 2732]. These chemicals are ubiquitous and commonly found in cleaning products, pest control products, and consumer products, such as plastics and toys [33]. Because of their smaller size, immature metabolic systems, exploratory behavior, extended periods spent on the floor and ground, and rapid physical and neurologic development and growth, children are not only more likely to experience disproportionate chemical exposures but also are more vulnerable to associated health effects [34].…”
Section: Introductionmentioning
confidence: 99%
“…Much academic research involves studies conducted by university researchers with the primary aim of peerreviewed publications. Exposure scientists and environmental epidemiologists have increasingly found this an interesting area, and some have been outspoken about using their research for public betterment via regulation and product changes (Dodson et al 2017;Zota et al 2017;Helm et al 2018).…”
Section: Biomonitoring and Household Exposure Researchmentioning
confidence: 99%